New Communication Approaches in the Digitalized World - Erciş, Mehmet Serdar (Cambridge Scholars Publisher, 2020)
The collection of essays reviews, explores and reports on the state of the digitalized world and a number of communication issues. It is a readable, non-technical publication which offers a comprehensive presentation of communication issues, trends, data, and likely future developments in the digitalized world.